Correlation Analysis of Knowledge and Education Against the Implementation of Basic Life Support (BHD) in Patients of Cardiac Arrest by Nurses in Emergency Installation and ICU of General Hospital of Dr. Soedarso Pontianak - Maulidah Maulidah; Dhelya Widasmara; Titin Andri Wihastuti (Research Journal of Life Science, 2020)
Cardiac arrest is a condition where the heart stopped abruptly, and this condition usually occurs in someone who has had heart disease or has never experienced it. In terms of clinical, someone who is experiencing a state of cardiac arrest found no signs of a palpable pulse and other signs of circulation. Efforts in terms of handling cases of the cardiac arrest itself need the role of nurse, one cardiac arrest treatment efforts by nurses are implementing Basic Life Support. The factors that affect the implementation of BHD itself is knowledge and education. The purpose of this research is analizing the correlation between knowledge and education on the implementation of BHD in cardiac arrest patients by nurses in the Emergency Installation and ICU of the General Hospital of Dr. Soedarso Pontianak. This study uses a cross-sectional approach with descriptive corelational type. The population in this study are 56 nurses. Sampling technique using total sampling. The result of this study, based on two variables: the knowledge and education have the same p-value that is p=0.000 or α <0.05. It means that there is a correlation between knowledge and education on the implementation of BHD in patients with cardiac arrest in General Hospital of Dr. Soedarso Pontianak.